Investigating the hatchability and nauplii biometry of Artemia franciscana in unconventional waters of Sistan region, Southeast Iran - Hashem Khandan Barani; Abdolali Rahdari; Narjes Sanchooli; Ali Khosravanizadeh (تغذیه آبزیان)
Introduction: Nowadays, using unconventional water, especially in arid and semi-arid areas, has increased as a result of global population increase, urbanization and climate change. Using these water sources for aquaculture is suggested for optimal utilization and reduction of their adverse effects on the environment. Artemia is an aquatic crustacean that is distributed all over the world. It plays an important role in the aquatic food chain due to containing a variety of high nutrients such as proteins, amino acids, fatty acids, vitamins and antioxidants. These organisms are the most common live-food item in the aquaculture industry to feed the larval stages of fish and crustaceans in different parts of the world. Artemia can grow in various saltwater environments. The water sources suitable for them do vary considerably in terms of ionic composition, climatic conditions, seasonality, productivity, altitude, and other characteristics. Among the species of the genus Artemia, A. franciscana is the most important one for aquaculture use, and it has been introduced in salt-waters for integrated Artemia–salt production. This species is characterized by the standard features of the short-life cycles: highly adaptable to adverse environmental conditions, easy cultivation and easy availability. The aim of this study was to investigate the feasibility of hatching and growth performances of Artemia (A. franciscana) in the unconventional water conditions in Sistan region, Southeast Iran under laboratory conditions. Materials and methods: The present study was carried out in the Laboratory of Reproduction and Breeding Aquatic Animals, Hamoun International Wetland Research Institute located in Zabol Research Institute in February 2024. Hatching rate, growth performance (comparison of body length and width), abundance of each biological form and health (comparison of morphological characteristics) of A. franciscana under breeding conditions of unconventional waters in Sistan region were investigated in this study. For this purpose, Artemia cysts were hatched in plastic jars using three replicated treatments, i.e., control (T1; distilled water + sea salt; 35.37 ppt), desalination wastewater (T2; 48.88 ppt), deep aquifer well water (T3; 16.35 ppt), and well water (T4; 28.46 ppt). All treatments were kept under standard conditions including temperature 27 °C, light 37 μmol/m2/s as well as 12 hours light and 12 hours darkness (12L:12D) during the experimental period. After 48 h of incubation, the hatching rate of Artemia cysts was analyzed. In order to evaluate growth performance and health status, at least 30 specimens from each treatment were randomly selected and photographed, then body length and width were measured using Digimizer software. Water quality parameters including temperature, pH, salinity, ammonia, nitrate, nitrite, sulfate, hardness, Cl, Mg and Cu were recorded using standard methods during the experiment. All data obtained in this study were analyzed using One-Way ANOVA, followed by Tukey's test for any significant differences among the treatments. Pearson’s correlation coefficient (r) was calculated for the statistical interpretation of the influence of the physicochemical variables on hatching rate and body length. Results and discussion: The results showed that hatchability of cysts and body length of Artemia were significantly different among treatments (p<0.05). The highest value of 71.32 ± 5.41% was recorded in T1 followed by 67.19 ± 4.28% in T3, 51.19 ± 2.33% in T4 and 47.81 ± 2.78% in T2 on the 48 h after cyst incubation. The length (mm) of Artemia was higher (0.64 ± 0.06) in T3 than in T1 (0.62 ± 0.05), T4 (0.59 ± 0.04) and T2 (0.56 ± 0.05). Instar 2 was the dominant form in T3 and T4, while instar 2 was the dominant form in the other two treatments. The morphological characteristics of Artemia were similar and normal between all treatments. The results showed that although the hatchability of cysts was more affected by the breeding environment, the growth of Artemia in all the unconventional water treatments was suitable compared to the control treatment, and also the morphological characteristics of Artemia were normal in all treatments. Due to the occurrence of long-term droughts in Sistan region, the only opportunity for the continuation of aquaculture, especially in recent years, lies in the use of unconventional saline water resources in this region. So, the present study provides the first evidence of relatively favorable hatching and suitable initial growth of Artemia in unconventional saline waters, especially desalination wastewater, in Sistan region and shows that cultivation Artemia is biologically possible in the unconventional waters under laboratory conditions. Conclusion: The data presented in this study generate the first useful information for the future inoculation of Artemia in unconventional waters (desalination wastewater, deep aquifer well water and well water) in Sistan, and hence domestic Artemia production in the country. However, further larger-scale laboratory work, followed by field trials, is still needed. Funding: The authors thank the Research Institute of Zabol for funding this study (Number: PR-RIOZ-1402-8853-1). Conflicts of interest: The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper. Acknowledgments: The author would like to thank the helpful assistance offered by the laboratory staff in Aquatic Sciences Department of Research Institute of Zabol.